2001
DOI: 10.1111/j.1945-5100.2001.tb01930.x
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐chromium formation intervals for chondrules from the Bishunpur and Chainpur meteorites

Abstract: Abstract-Whole-chondrule Mn-Cr isochrons are presented for chondrules separated from the Chainpur (LL3.4) and Bishunpur (LL3.1) meteorites. The chondrules were initially surveyed by instrumental neutron activation analysis. LL-chondrite-normalized Mn/Cr, Mn/Fe, and Sc/Fe served to identify chondrules with unusually high or low MdCr ratios, and to correlate the abundances of other elements to Sc, the most refractory element measured. A subset of chondrules from each chondrite was chosen for analysis by a scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 57 publications
5
62
0
Order By: Relevance
“…A complete digestion of fluoride complexes and Cr-rich refractory phases, such as spinel, is ensured by a subsequent dissolution in aqua regia (concentrated HCl and HNO 3 mixture in 3 : 1 ratio). The Cr purification technique is adapted from Birck & Allegre (1985), Lugmair & Shukolyukov (1998), Glavin et al (2004), Nyquist et al (2001), Ueda et al (2006), and Trinquier et al (2007), and has already been described in Yin et al (2007). Cr was separated from the major elements by elution through cationic-exchange resin in HCl medium.…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete digestion of fluoride complexes and Cr-rich refractory phases, such as spinel, is ensured by a subsequent dissolution in aqua regia (concentrated HCl and HNO 3 mixture in 3 : 1 ratio). The Cr purification technique is adapted from Birck & Allegre (1985), Lugmair & Shukolyukov (1998), Glavin et al (2004), Nyquist et al (2001), Ueda et al (2006), and Trinquier et al (2007), and has already been described in Yin et al (2007). Cr was separated from the major elements by elution through cationic-exchange resin in HCl medium.…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%
“…We can see that the value of the bulk CI is also in this zone. 53 m However, Yin et al (2007) recently revised Nyquist et al (2001) ages of chondrules (Kita et al 2005), and resolved a major discrepancy in the chronology of the early solar system.…”
Section: Delayed Chondrule Formation For Ordinary Chondritesmentioning
confidence: 99%
“…The 53 Cr systematics in various solar system objects show that 53 Mn was alive in the early solar system and therefore, the 53 Cr system can be used as a chronometer among objects that had a constant 53 Mn/ 55 Mn initial ratio Shukolyukov 1998, 2001;Carlson and Lugmair 2000;Nyquist et al 2001). In the case of IIIAB iron meteorites, studies by Davis and Olsen (1990), Hutcheon and Olsen (1991), and Hutcheon et al (1992) showed that 53 Mn was alive in these meteorites.…”
Section: Introductionmentioning
confidence: 99%
“…The exposure age of NWA 753 is 25 Ma (Ebisawa et al, 2003) and hence the cosmogenic effect is expected to be slightly smaller than that in Sahara 99531. The insignif- icance of the cosmogenic effect in ordinary chondrites was shown based on the production rate of 53 Mn by cosmic-ray spallation reactions (Nyquist et al, 2001). Hsu (2005) also reached a similar conclusion that the cosmogenic effect is negligible in the case of pallasite olivine.…”
Section: Resultsmentioning
confidence: 48%
“…The inferred initial 53 Mn/ 55 Mn ratio is (1.84 ± 0.42(2σ )) × 10 −6 . This translates to an age of 2.1 Ma before the angrite LEW 86010 (Lugmair and Shukolyukov, 1998) and 8.7 Ma after chondrules in ordinary chondrites (Nyquist et al, 2001 …”
Section: Resultsmentioning
confidence: 99%